Fabrication of photoactive heterostructures based on quantum dots decorated with Au nanoparticles. Issue 1 (1st December 2016) - Fanizza, Elisabetta; Urso, Carmine; Iacobazzi, R. Maria; Depalo, Nicoletta; Corricelli, Michela; Panniello, Annamaria; Agostiano, Angela; Denora, Nunzio; Laquintana, Valentino; Striccoli, Marinella; Curri, M. Lucia
Abstract: Silica based multifunctional heterostructures, exhibiting near infrared (NIR) absorption (650–1200 nm) and luminescence in the visible region, represent innovative nanosystems useful for diagnostic or theranostic applications. Herein, colloidal synthetic procedures are applied to design a photoactive multifunctional nanosystem. Luminescent silica (SiO2 ) coated quantum dots (QDs) have been used as versatile nanoplatforms to assemble on their surface gold (Au) seeds, further grown into Au spackled structures. The synthesized nanostructures combine the QD emission in the visible region, and, concomitantly, the distinctive NIR absorption of Au nanodomains. The possibility of having multiple QDs in a single heterostructure, the SiO2 shell thickness, and the extent of Au deposition onto SiO2 surface have been carefully controlled. The work shows that a single QD entrapped in 16 nm thick SiO2 shell, coated with Au speckles, represents the most suitable geometry to preserve the QD emission in the visible region and to generate NIR absorption from metal NPs. The resulting architectures present a biomedical potential as an effective optical multimodal probes and as promising therapeutic agents due to the Au NP mediated photothermal effect. Abstract :